Strategi Peningkatan Hasil Belajar Fikih melalui Problem Based Learning pada Siswa Kelas VI Madrasah Ibtidaiyah - Eli Sumarni (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This classroom action research was conducted because the level of student learning completion in the Fiqh subject was still low, namely only 59% of students achieved the Minimum Completion Criteria (KKM). By implementing the Problem Based Learning (PBL) method in Fiqh learning, it is expected to improve student learning outcomes in accordance with the expected learning objectives. The formulation of the problem in this study includes: how to implement Fiqh learning using the PBL method, and how to improve student learning outcomes after implementing the method at MI Muhammadiyah Basin. This study follows the stages in the classroom action model, namely: planning, implementing actions, observation, and reflection. The subjects of this study were grade VI students of MI Muhammadiyah Basin in the Fiqh subject. The results of this study indicate that the application of the PBL method with stages such as compiling problems or questions that must be solved by students, can encourage improved learning outcomes. This can be seen from the data obtained in cycles I and II. In cycle I, the percentage of students who achieved KKM was 70.59%, while in cycle II it increased to 94.18%. Based on these improvements, it can be concluded that the application of the Problem Based Learning method in Islamic Jurisprudence learning has succeeded in improving student learning outcomes at MI Muhammadiyah Basin.